SELF EFICATION OF PEOPLE WITH DISABILITIES IN IMPROVING DIGITAL LITERATIONS (Study in Jayapura City, Papua Province) - Rieka Mustika; Bambang Mudjiyanto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Abstrak. Penelitian ini bertujuan mendapatkan gambaran mengenai efikasi diri peserta Jambore ICT Tahun 2016 dan 2017 penyandang disabilitas dalam pemanfaatan teknologi informasi dan komunikasi. Beberapa aspek yang dihadapi penyandang disabilitas saat ini antara lain: kesulitan melihat, kesulitan mendengar, kesulitan berjalan/naik tangga, kesulitan menggunakan/menggerakkan tangan/jari, kesulitan dalam hal mengingat atau berkonsentrasi, gangguan perilaku dan/atau emosional, kesulitan/gangguan berbicara dan/atau memahami/berkomunikasi dengan orang lain, dan kesulitan mengurus diri. Penyandang disabilitas sebagai sumber daya manusia seharusnya dikembangkan potensi dan kelebihan dirinya. Dengan pemanfaatan ICT sebagai enabler diharapkan dapat meningkatkan efikasi diri para peserta Jambore penyandang disabilitas untuk hidup mandiri di dunia kerja. Penelitian ini menggunakan metode deskriptif kualitatif untuk mendapatkan mengenai self efficacy pada penyandang disabilitas yang mengikuti Jambore ICT. Pengumpulan data lapangan berlangsung dari tanggal 30 Juli 2018 s/d 3 Agustus 2018, Kota Jayapura, Provinsi Papua. Subyek penelitian individu, dengan key informan dan informan ditarik melalui snowball sampling. Keikutsertaan pelatihan ICT disabilitas (tunarungu, tunadaksa, dan tunanetra) dalam Jambore ICT Tahun 2016 dan 2017 dapat meningkatkan keyakinan atas kemampuan dirinya memasuki dunia kerja, mensosialisasikan kepada saudara, teman dan masyaraakat serta dapat menumbuhkan keyakinan dalam tentukan kesulitan, seperti pengoperasian software dan hardware ICT. Pemisahan jenis dan klasifikasi disabilitas dengan jumlah siswa pelatihan dalam satu kelas yang standar akan mempermudah penerimaan materi pelatihan Jambore ICT. Abstract. This study aims to get a picture of the self-efficacy of ICT participants in 2016 and 2017 with disabilities in the use of information and communication technology. Some aspects faced by persons with disabilities today include: difficulty seeing, difficulty in hearing, difficulty walking / climbing stairs, difficulty using / moving hands / fingers, difficulty in remembering or concentrating, behavioral and / or emotional disturbances, difficulty in speaking and / or understand / communicate with others, and have difficulty taking care of yourself. Persons with disabilities as human resources should develop their potential and strengths. The use of ICT as an enabler is expected to increase the self-efficacy of Jamboree participants with disabilities to live independently in the world of work. This study uses a qualitative descriptive method to obtain self efficacy in persons with disabilities who take the ICT Jamboree. Field data collection took place from 30 July 2018 to 3 August 2018, Jayapura City, Papua Province. Individual research subjects, with key informants and informants drawn through snowball sampling. The participation of ICT disability training (deaf, deaf, and blind) in the 2016 and 2017 ICT Jamboree can increase confidence in her ability to enter the workforce, socialize with relatives, friends and communities and can foster confidence in determining difficulties, such as the operation of ICT software and hardware. Separation of types and classifications of disability with the number of training students in a standard class will facilitate the reception of ICT Jambore training materials.